Trade reforms and food security : (FAO, 2003)
The purpose of this book is to examine the linkages between trade liberalization, economic openness and poverty, to enhance food security status of poor countries. The book comprises 4 parts. Part 1 introduces theories and definitions related to the concept of food security and its measurement, and to the gains from trade liberalization, before discussing how trade and food security are related at a theoretical level. Part 2 identifies specific issues and debates related to globalization in the context of the imbalance between developing and developed countries in the levels of agricultural protection. Part 3 discusses both the types of methodological approach that have been used in analysing the impact of economic and trade liberalization, and the implementation of policy and institutional reforms in Africa, Asia, Latin America, and the transition economies. Part 4 provide a framework for further research.